1994
DOI: 10.1016/0014-5793(94)00937-6
|View full text |Cite
|
Sign up to set email alerts
|

Mutations to kirromycin resistance occur in the interface of domains I and III of EF‐Tu·GTP

Abstract: The antibiotic kirromycin inhibits protein synthesis by binding to EF-Tu and preventing its release from the ribosome after GTP hydrolysis. We have isolated and sequenced a collection of kirromycin resistant tuf mutations and identified thirteen single amino acid substitutions at seven different sites in EF-Tu. These have been mapped onto the 3D structures of EF-Tu'GTP and EF-Tu.GDP. In the active GTP form of EF-Tu the mutations cluster on each side of the interface between domains I and III. We propose that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 27 publications
5
46
0
Order By: Relevance
“…The kirromycin binding site is located at the interface between domains I and III of EF-Tu (12) (see Fig. S1 in the supplemental material), and previous studies have identified Kir r mutations at this interface (28). These observations are consistent with the proposal that domains I and III are dynamic with respect to one another (29).…”
Section: Resultssupporting
confidence: 84%
“…The kirromycin binding site is located at the interface between domains I and III of EF-Tu (12) (see Fig. S1 in the supplemental material), and previous studies have identified Kir r mutations at this interface (28). These observations are consistent with the proposal that domains I and III are dynamic with respect to one another (29).…”
Section: Resultssupporting
confidence: 84%
“…Substitution mutations at three amino acid sites in domain I of EF-Tu, Leu 12°, Gln 124, TyP 6° give rise to a kirromycin resistant phenotype [13]. The side chains of these three amino acids are aligned and in contact, Gln with Leu and Leu with Tyr, and all point into the domain I-III interface in both the GTP and GDP conformations of EF-Tu [1,31].…”
Section: Discussionmentioning
confidence: 99%
“…The basis of the causal relationship between kirromycin resistance and reduced affinity for aa-tRNA may be the location of the mutations in the domain interface, a location which could plausibly affect the conformational switching of EF-Tu, reducing its affinity for both ligands. This interpretation would suggest that though mutations to kirromycin resistance map to both sides of the domain I-III interface [13], the actual binding site of kirromycin might be elsewhere, for example on domain I, but be influenced by the interdomain interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to kirromycin is usually achieved by single amino acid substitutions in highly conserved positions of EFTu. These mutations cluster in or near the interface between domains I and III of EF-Tu⅐GTP (1,19), a region where the antibiotic was recently found to bind (38). Superposition of the EF-Tu2 amino acid sequence on the crystal structure of Thermus thermophilus EF-Tu⅐GppNHp (3) revealed that no deviating residues are present at the interface between domains I and III, although kirromycin resistance due to residues elsewhere in the protein cannot be excluded.…”
Section: Vol 184 2002 S Ramocissimus Tuf2 Encodes a Minor Ef-tu 4215mentioning
confidence: 99%